2022
DOI: 10.1557/s43580-022-00208-3
|View full text |Cite
|
Sign up to set email alerts
|

PDMS composites with photostable NIR dyes for multi-modal ultrasound imaging

Abstract: All-optical ultrasound (OpUS) imaging has emerged as an imaging paradigm well-suited for minimally invasive surgical procedures. With this modality, ultrasound is generated when pulsed or modulated light is absorbed within a coating material. By engineering wavelength-selective coatings, complementary imaging and therapeutic modalities can be integrated with OpUS. Here, we present a wavelength-selective composite material comprising a near-infrared absorbing dye and polydimethylsiloxane. The optical absorption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Further, the OpUS generating coating can be engineered with composite materials that have wavelength-selective absorption which could allow for imaging and therapy to be implemented through a single multimode fibre, thereby integrating therapy and ultrasound generation while decreasing the lateral device dimensions and increasing the mechanical flexibility. As previously reported, several materials can realise high optical absorption at a specific wavelength (532 nm 39 and 1064 nm 58 ) for ultrasound generation, and low optical absorption at another wavelength (e.g., 808 nm) for transmission of laser light for optical ablation. In addition, attributed to the high degree of device miniaturisation, multiple sensing and imaging techniques can be coupled with the probe within the medical catheter, offering comprehensive guidance for optical ablation treatment.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Further, the OpUS generating coating can be engineered with composite materials that have wavelength-selective absorption which could allow for imaging and therapy to be implemented through a single multimode fibre, thereby integrating therapy and ultrasound generation while decreasing the lateral device dimensions and increasing the mechanical flexibility. As previously reported, several materials can realise high optical absorption at a specific wavelength (532 nm 39 and 1064 nm 58 ) for ultrasound generation, and low optical absorption at another wavelength (e.g., 808 nm) for transmission of laser light for optical ablation. In addition, attributed to the high degree of device miniaturisation, multiple sensing and imaging techniques can be coupled with the probe within the medical catheter, offering comprehensive guidance for optical ablation treatment.…”
Section: Discussionmentioning
confidence: 68%
“…Previous studies have shown that these ultrasound generating coatings are stable for continuous use over extended periods (ca. 1 h) 58 , much longer than those used during these studies.…”
Section: Methodsmentioning
confidence: 88%
“…OpUS has shown promise for multi-modal devices, with previous studies including a combination with photoacoustic imaging [ 11 ] and optical ablation [ 10 ]. The presented probe could be modified to incorporate a secondary modality by using a wavelength-selective coating such as those previously presented from PDMS-AuNP [ 7 ] or PDMS-Epolight [ 12 ]. Additionally, the probe could be adapted to provide rotational ultrasound imaging similar to those demonstrated in previous studies [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…A majority of the devices demonstrated to date have utilised a forward-viewing configuration for synthetic aperture imaging in both two- [ 3 , 12 15 ] and three- [ 7 , 16 ] dimensions. Additionally, there have been a small number of studies in which in vivo tissue imaging was performed with devices suitable for minimally invasive imaging [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%